Polyacrylamide gel electrolyte as well as preparation method and application thereof
By using polyacrylamide gel electrolyte to prepare a portable corrosive three-electrode sensor, the problem of evaporation or leakage of traditional liquid electrolytes is solved, the stability and sensitivity of the sensor are improved, and effective monitoring of the corrosion state of metal is achieved.
Patent Information
- Application Number
- CN202411437167.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-10-15
AI Technical Summary
In the corrosion research in the field of cultural and architectural fields, traditional liquid electrolytes are prone to evaporation or leakage during long-term use, resulting in unstable and inaccurate monitoring data. The stability and conductivity of existing polymer electrolytes under different environmental conditions still need to be further optimized.
Polyacrylamide gel electrolyte is used, which consists of acrylamide monomer, initiator, crosslinking agent and glycerol. It is radically polymerized under aqueous phase conditions to form a stable gel electrolyte, which is used to prepare a portable corrosion triple electrode sensor.
The polyacrylamide gel electrolyte works stably under different environmental conditions, improving the sensitivity and response speed of the sensor, effectively monitoring the corrosion state of metals, extending the monitoring timeliness, and improving the reliability and durability of the sensor.
Smart Images

Figure CN119552302A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polyacrylamide gel electrolyte and a preparation method and application thereof, belonging to the field of metal corrosion monitoring. Background Art
[0002] Electrochemical testing technology has been widely used in corrosion research. However, these technologies have some special difficulties in corrosion research in the field of cultural buildings. General tests are to prepare artificial materials to imitate the original composition of metals and use traditional laboratory techniques for research. However, the information provided by these is also limited because it is impossible to completely reproduce the composition formed on the buildings over a long period of time. How to non-destructively monitor corrosion information has become a research focus.
[0003] Traditional liquid electrolytes are prone to evaporation or leakage during long-term use, resulting in unstable and inaccurate monitoring data.
[0004] In the field of atmospheric corrosion monitoring, the use of polymer electrolytes instead of traditional liquid electrolytes has become a common and effective method. This alternative is particularly important in the design and application of portable corrosion sensors because it can effectively avoid the risks of liquid leakage or evaporation. In the field of monitoring, there are still some problems that need to be solved. First, the stability and conductivity of existing polymer electrolytes under different environmental conditions still need to be further optimized to ensure the accuracy of long-term monitoring. Secondly, how to improve the sensitivity and response speed of the sensor to capture tiny corrosion changes is also the focus of current research. Summary of the invention
[0005] Purpose of the invention: The first purpose of the present invention is to provide a polyacrylamide gel electrolyte, the second purpose of the present invention is to provide a method for preparing the polyacrylamide gel electrolyte, the third purpose of the present invention is to provide an application of the polyacrylamide gel electrolyte in the preparation of a portable corrosion three-electrode sensor, and the fourth purpose of the present invention is to provide a portable corrosion three-electrode sensor based on the polyacrylamide gel electrolyte to overcome the difficulties associated with in-situ testing using liquid electrolytes, especially in the field of atmospheric corrosion monitoring.
[0006] Technical solution: The polyacrylamide gel electrolyte described in the present invention comprises acrylamide monomer, initiator, cross-linking agent and glycerol as raw materials, the acrylamide monomer is dissolved in water phase conditions, the initiator and cross-linking agent are added, and the acrylamide is free radical polymerized by the initiator under anaerobic conditions to obtain the electrolyte.
[0007] Furthermore, the initiator is ammonium persulfate or potassium persulfate.
[0008] Furthermore, the cross-linking agent is methylene bisacrylamide.
[0009] Furthermore, the aqueous phase is a sodium sulfate solution or a rain-like aqueous solution, the concentration of the sodium sulfate solution is 0.002-1 mol / L, and the concentration of the total solute in the rain-like aqueous solution is 0.0005-0.05 mol / L.
[0010] Furthermore, the rain-imitation water solution contains calcium sulfate, ammonium sulfate, ammonium chloride and sodium nitrate.
[0011] Furthermore, the concentration of acrylamide monomer in the water phase is 10-50%, the amount of initiator used is 4-6% of the monomer mass, and the amount of crosslinking agent used is 0.01-0.5% of the monomer mass.
[0012] The method for preparing the polyacrylamide gel electrolyte of the present invention comprises the following steps:
[0013] Dissolve acrylamide in water phase, add initiator, crosslinker, glycerol and sodium sulfate solution, stir evenly, bubble inert gas for 10-20 minutes, place at 60-100° C. for 30-60 minutes, and cool to room temperature to obtain polyacrylamide gel electrolyte.
[0014] The invention discloses an application of the polyacrylamide gel electrolyte in preparing a portable corrosion three-electrode sensor.
[0015] The present invention also includes a portable three-electrode corrosion sensor based on the polyacrylamide gel electrolyte of the present invention, comprising an outer mold, the outer mold is filled with the polyacrylamide gel electrolyte of the present invention, the polyacrylamide gel electrolyte of the present invention is inserted with a counter electrode and a reference electrode, and the bottom of the polyacrylamide gel electrolyte of the present invention is provided with a working electrode.
[0016] Furthermore, the outer mold is made of epoxy resin and hardener, the reference electrode is a silver / silver chloride electrode, a silver wire electrode or a silver-plated silver wire electrode, the electrode is a carbon rod or a carbon plate, and the working electrode is a stainless steel sheet.
[0017] Furthermore, the reference electrode is arranged in parallel with the counter electrode, and the bottom end of the reference electrode is 2 to 6 mm away from the upper surface of the working electrode.
[0018] Furthermore, the outer layer mold is formed by mixing epoxy resin and hardener and pouring the mixture into a silicone mold and letting it stand for 24 to 48 hours.
[0019] Furthermore, the working electrode needs to be pretreated, and the pretreatment steps include: ultrasonically treating the working electrode in acetone, ethanol, and deionized water for 20 to 40 minutes each until it is clean, drying the treated working electrode at 40 to 60° C. for 1 to 2 hours, and polishing the dried working electrode with 280#, 800#, and 1200# sandpapers in turn.
[0020] The present invention also includes the application of the polyacrylamide gel electrolyte of the present invention or the portable corrosion three-electrode sensor of the present invention in atmospheric corrosion monitoring.
[0021] The polyacrylamide gel electrolyte used in the present invention can perform non-destructive monitoring of metals and evaluate their corrosion status in real time, thereby providing a scientific basis for the maintenance and protection of metal materials, extending their service life, and reducing potential safety risks. By adding glycerol, the electrolyte not only improves its moisture retention performance, but also extends the timeliness of monitoring, so that the electrolysis can work stably under long-term environmental conditions. This improvement not only improves the reliability and durability of sensors based on polyacrylamide gel electrolytes, but this feature enables the electrolyte to continuously and effectively monitor the corrosion status of metal materials in practical applications, providing a more effective solution for real-time monitoring of the corrosion status of metal materials in the atmosphere, and providing reliable data support for the implementation of anti-corrosion measures, thereby ensuring the safety and durability of metal structures, and providing a scientific basis for the formulation of relevant anti-corrosion measures.
[0022] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0023] (1) The polyacrylamide gel electrolyte of the present invention has good stability and a simple preparation method, and has the following advantages: ① Electrolyte stability: The acrylamide gel electrolyte can be stored for a certain period of time, which is suitable for multiple tests, thereby improving the flexibility and efficiency of the experiment. ② The moisturizing performance of the glycerol gel electrolyte is enhanced by adding glycerol, so that the electrolyte can maintain a stable state under various environmental conditions, thereby achieving long-term monitoring. This improvement improves the reliability and durability of the sensor.
[0024] (2) The advantage of the portable corrosion three-electrode sensor provided by the present invention is that it can realize non-destructive testing and is convenient for corrosion monitoring in different environments. The specific advantages include: ① The sensor is designed to be portable, which is convenient for rapid on-site detection and reduces damage to the sample. ② Good repeatability: The sensor has good stability. When the same sample is tested three times in a row, the results are not much different, showing its reliable measurement ability. ③ Optimizing the position layout of the electrodes in the gel electrolyte and using carbon plates as counter electrodes can help to evenly distribute the electric field between the electrodes, thereby reducing interference and improving measurement accuracy. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the structure of the portable three-electrode corrosion sensor of the present invention;
[0026] Figure 2 Electrochemical impedance spectra and Tafel comparison diagrams of five groups of portable three-electrode corrosion sensors with different sodium sulfate contents based on polyacrylamide gel electrolyte prepared in Example 2;
[0027] Figure 3 Electrochemical impedance spectra and Tafel comparison diagrams of five groups of portable three-electrode corrosion sensors based on polyacrylamide gel electrolyte prepared in Example 3;
[0028] Figure 4 This is a graph showing the effective use time test results of 5 groups of portable three-electrode corrosion sensors based on polyacrylamide gel electrolyte prepared in Example 3;
[0029] Figure 5 A comparison diagram of electrochemical impedance spectra of three groups of portable corrosion three-electrode sensors based on polyacrylamide gel electrolyte prepared in Example 4;
[0030] Figure 6 A comparison diagram of electrochemical impedance spectra of three groups of portable corrosion three-electrode sensors based on polyacrylamide gel electrolyte prepared in Example 5;
[0031] Figure 7 This is the stability electrochemical impedance spectrum of the portable corrosion three-electrode sensor based on polyacrylamide gel electrolyte prepared in Example 6;
[0032] Figure 8 Electrochemical impedance spectra and TAFEL comparison diagram of 7 groups of corrosion three-electrode sensors based on agar gel electrolyte prepared in Comparative Example 1;
[0033] Fig. 9 The figure is the stability test result of the best ratio in Comparative Example 1 for two consecutive days;
[0034] Fig.10 Electrochemical impedance spectra of the portable three-electrode corrosion sensor based on polyacrylamide gel electrolyte and the three-electrode corrosion sensor based on agar gel electrolyte in Example 7 for corrosion of different metal blocks within 24 hours;
[0035] Fig.11 This is a corrosion rate diagram of the corrosion of different metal blocks within 24 hours using the hanging plate method in Example 7. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0037] Example 1
[0038] like Figure 1 As shown, the portable three-electrode corrosion sensor based on polyacrylamide gel electrolyte of the present invention comprises an outer mold 1, in which the polyacrylamide gel electrolyte 5 of the present invention is installed, and the polyacrylamide gel electrolyte 5 of the present invention is inserted with a counter electrode 2 and a reference electrode 3. A working electrode 4 is provided at the bottom of the polyacrylamide gel electrolyte 5 of the present invention.
[0039] The reference electrode 3 is arranged in parallel with the electrode 2, the distance between the reference electrode 3 and the electrode 2 is 2 cm, and the distance between the reference electrode 3 and the electrode 4 is 2 to 6 mm. The distance between the counter electrode 2 and the electrode 4 is longer (about 1 mm longer) than the distance between the reference electrode 3 and the electrode 4. The outer mold 1 is made of 25 mL of epoxy resin glue E44 (Dongguan Eric New Materials Co., Ltd.) and 25 mL of epoxy curing agent 650 (Dongguan Eric New Materials Co., Ltd.) mixed and poured into a double-layer cylindrical silicone mold with an inner diameter of 4 cm, an outer diameter of 5 cm, a height of 6 cm, and a layer thickness of 5 mm, and then left to stand for 30 hours. The reference electrode 3 is a silver / silver chloride electrode, the electrode 2 is a carbon rod, and the working electrode 4 is a stainless steel sheet with a length × width × thickness of 5 cm × 5 cm × 0.2 cm. The pretreatment process of the working electrode 4 is specifically as follows: the working electrode 4 is ultrasonically treated in acetone, ethanol, and deionized water for 30 minutes each until it is clean, and then the cleaned working electrode 4 is polished in turn with 280#, 800#, and 1200# sandpapers, and finally the treated working electrode 4 is dried in a 60°C oven for 2 hours to obtain the working electrode 4.
[0040] Example 2 Preparation of a portable corrosion three-electrode sensor using the polyacrylamide electrolyte described in Example 1 at different sodium sulfate concentrations
[0041] (1) Preparation of polyacrylamide gel electrolyte with a sodium sulfate concentration of 0.002 mol / L
[0042] First, 2.84 mg of sodium sulfate was weighed and dissolved in 10 mL of water to obtain a sodium sulfate solution. Then, 2 g of acrylamide, 0.1 g of ammonium persulfate, and 2.5 mg of methylenebisacrylamide were weighed and dissolved in the sodium sulfate solution. The mixed solution was deoxygenated with nitrogen for 10 minutes, and then heated at 60°C for 30 minutes for polymerization. The mixture was poured into a cylindrical silica gel mold with a diameter of 40 mm and a height of 40 mm, and cooled to obtain a polyacrylamide gel electrolyte.
[0043] (2) The polyacrylamide obtained in step (1) is poured into a mold 1 in which a counter electrode 2 and silver / silver chloride as a reference electrode 3 are inserted, and then the mold 1 with the gel electrolyte is placed on the working electrode 4 to form a portable corrosion three-electrode sensor. The distance between the reference electrode 3 and the electrode 4 is 4 mm, and the distance between the counter electrode 2 and the electrode 4 is 5 mm.
[0044] Using the above process, four sets of portable corrosion three-electrode sensors with polyacrylamide gel electrolytes having sodium sulfate concentrations of 0.02 mol / L, 0.2 mol / L, 0.5 mol / L, and 1 mol / L were prepared.
[0045] The electrochemical performance of the five groups of polyacrylamide gel electrolyte corrosion three-electrode sensors in this example was tested to study their influence on the working electrode. The test results are as follows: Figure 2 shown. Figure 2 The electrochemical impedance spectra and Tafel comparison diagrams of 5 groups of portable corrosion three-electrode corrosion sensors with different sodium sulfate contents based on polyacrylamide gel electrolyte prepared in Example 2, wherein Figure A is an electrochemical impedance spectrum diagram and Figure B is a Tafel diagram. Figure 2 It can be seen from Figure A that as the sodium sulfate content increases, the capacitive reactance arc gradually decreases. When the sodium sulfate concentration changes between 0.2mol / L and 1mol / L, the change range of the capacitive reactance arc is relatively small. This phenomenon shows that within this concentration range, the influence of the electrolyte tends to be stable. Therefore, after comprehensive consideration, 0.5mol / L sodium sulfate is selected as the optimal concentration of the electrolyte. This concentration can ensure good conductivity while avoiding the adverse effects that may be caused by excessive concentration, thereby providing a more reliable electrochemical environment for subsequent corrosion monitoring.
[0046] Example 3 Preparation of polyacrylamide gel electrolytes with different glycerol concentrations
[0047] The preparation process is the same as in Example 1, except that the concentration of glycerol is changed as follows:
[0048] (1) Preparation of polyacrylamide gel electrolyte with a glycerol content of 30% W / W
[0049] First, 0.710 g of sodium sulfate was weighed and dissolved in 10 mL of water to obtain a sodium sulfate solution with a concentration of 0.5 mol / L, and then 2 g of acrylamide, 0.1 g of ammonium persulfate, and 2.5 mg of methylenebisacrylamide were weighed and dissolved in the sodium sulfate solution to obtain a uniform mixed solution. Glycerol with a concentration of 30% W / W was added to the mixed solution, and the mixed solution was deoxygenated for 10 min using nitrogen, and then heated at 60° C. for 30 min for polymerization, poured into a cylindrical silica gel mold with a diameter of 40 mm and a height of 40 mm, and cooled to obtain a polyacrylamide gel electrolyte.
[0050] (2) The polyacrylamide obtained in step (1) is poured into a mold 1 having a counter electrode 2 and silver / silver chloride as a reference electrode 3 inserted therein, and the mold 1 with the gel electrolyte is then placed on the working electrode 4 to form a portable corrosion three-electrode sensor.
[0051] Using the above process, four sets of portable corrosion three-electrode sensors with polyacrylamide gel electrolytes having glycerol contents of 0% W / W, 10% W / W, 20% W / W and 40% W / W were prepared respectively.
[0052] The electrochemical performance of the five groups of polyacrylamide gel electrolyte corrosion three-electrode sensors implemented in this case was tested. The test results are as follows: Figure 3 shown. Figure 3 The electrochemical impedance spectra and Tafel comparison diagrams of the five groups of portable three-electrode corrosion sensors based on polyacrylamide gel electrolyte prepared in Example 3, wherein A is the electrochemical impedance spectra of polyacrylamide gel electrolytes with different glycerol contents, and B is the Tafel diagram of polyacrylamide gel electrolytes with different glycerol contents. Figure 3 It can be observed from the data that the curve characteristics of all different glycerol concentrations show similar trends, which indicates that the addition of glycerol does not significantly change the characteristics of the electrode reaction, thus supporting the effectiveness of using this gel electrolyte for electrochemical testing.
[0053] Further analysis of the EIS and Tafel test results revealed that as the glycerol content gradually increased, the corrosion effect of the gel electrolyte on the working electrode gradually decreased, and the performance of the sensor also improved. This phenomenon shows that an appropriate amount of glycerol can effectively improve the stability and corrosion resistance of the electrolyte, but when the glycerol content exceeds 40%, the electrolyte exhibits higher softening characteristics and viscosity, making it unsuitable for use in experiments. Therefore, based on the electrochemical test results and the state of the electrolyte during actual use, it is more appropriate to select a gel electrolyte with a glycerol content of 30%-40% for testing.
[0054] Figure 4 The test results of the effective use time of 5 groups of portable three-electrode corrosion sensors based on polyacrylamide gel electrolyte prepared in Example 3 are shown, among which A is a statistical graph of the impedance test of sensors without glycerol added at different test times, B is a statistical graph of the impedance test of sensors with 10% glycerol added at different test times, C is a statistical graph of the impedance test of sensors with 20% glycerol added at different test times, D is a statistical graph of the impedance test of sensors with 30% glycerol added at different test times, and E is a statistical graph of the impedance test of sensors with 40% glycerol added at different test times. Figure 4It can be clearly seen that as the glycerol content increases to 30%, the effective use time of the polyacrylamide gel electrolyte corrosion sensor is also extended accordingly. Figure 4 Figure E is a statistical chart of the impedance test of the sensor with 40% glycerol added for 30 days. During the first 11 days of the test, the test results of the sensor remained stable and did not change, showing that it can effectively monitor corrosion during this period. Over time, the moisturizing effect of the electrolyte gradually decreases, which may cause it to undergo a phase change, thereby increasing conductivity and reducing impedance, and gradually increasing the corrosion effect on stainless steel.
[0055] In summary, the sensor was able to effectively monitor corrosion for up to 11 days. This result further verified the important role of glycerol in improving the long-term monitoring capability of polyacrylamide gel electrolytes and provided a solid foundation for its application in atmospheric corrosion monitoring.
[0056] Example 4 Preparation of gel corrosion three-electrode sensor with different electrodes
[0057] The basic steps for preparing the polyacrylamide gel corrosion sensor are the same as those in Example 3. In this example, the concentration of glycerol is set to 40% W / W. The difference is that the counter electrode 2 used is a carbon plate, and the reference electrode 3 is a silver / silver chloride electrode, a silver wire electrode, and a silver wire plated silver chloride electrode, thereby preparing three different sets of portable corrosion three-electrode sensors based on polyacrylamide gel.
[0058] The three sets of corrosion three-electrode sensors were electrochemically tested, and the results are as follows: Figure 5 shown. Figure 5 The electrochemical impedance spectra of the three groups of corrosion sensors prepared in Example 4 are compared. Figure 5 It can be seen that the curve characteristics of the three reference electrodes are basically the same, indicating that replacing reference electrode 3 does not significantly affect the corrosion test results. This discovery provides more possibilities for the flexible application of sensors, allowing the selection of suitable reference electrodes under different experimental conditions without affecting the accuracy of the test.
[0059] In summary, the results of this example further verified the reliability and adaptability of the polyacrylamide gel corrosion sensor, and laid a foundation for future research and application.
[0060] Example 5 Effect of different distances between reference electrode and working electrode on gel corrosion of three-electrode sensor
[0061] The basic steps for preparing the polyacrylamide gel corrosion sensor are the same as those in Example 4. In this example, the concentration of glycerol is set to 40% W / W. The counter electrode 2 used is a carbon plate. The difference is that the reference electrode 3 uses a silver / silver chloride electrode. In combination with practical applications, the distances between the reference electrode 3 and the working electrode 4 are selected to be 2 mm, 4 mm, and 6 mm, respectively, thereby preparing three different sets of portable corrosion three-electrode sensors based on polyacrylamide gel. The three sets of corrosion three-electrode sensors were subjected to electrochemical tests, and the results are as follows: Figure 6 shown. Figure 6 The electrochemical impedance spectra of the three groups of corrosion sensors prepared in Example 5 are compared, where A is the Nyquist plot and B is the Bode plot. Figure 6 As can be seen in Figure A, the curve characteristics of the three reference electrodes are basically the same, indicating that the electrode spacing has little effect on the overall characteristics of the electrochemical reaction. Figure 6 The rise of impedance in the low-frequency region of the Bode plot indicates that the electrolyte resistance gradually increases, which shows that the conductivity of the electrolyte is affected by the distance. Combined with actual tests, although the distance of different reference electrodes has little effect on the characteristic curve of the electrochemical reaction, the resistance of the electrolyte is indeed affected. Therefore, considering the actual test, choosing 4mm as the distance between the reference electrode and the working electrode can effectively ensure the effectiveness and repeatability of the experiment.
[0062] Example 6 Effect of different solutions on gel corrosion of three-electrode sensor
[0063] The basic steps for preparing the polyacrylamide gel corrosion sensor are the same as those in Example 2, except that a rain-like aqueous solution is used as the aqueous phase when preparing the polyacrylamide gel electrolyte, and the concentration of the total solute in the rain-like aqueous solution is 0.00073 mol / L, as follows.
[0064] (1) Prepare rainwater-like electrolyte
[0065] First, 14.43 mg of calcium sulfate dihydrate (CaSO4·2H2O), 15.04 mg of ammonium sulfate [(NH4)2SO4], 19.15 mg of ammonium chloride [(NH4)Cl], and 15.13 mg of sodium nitrate (NaNO3) were dissolved in 1000 mL of distilled water. The mixed solution was used as a liquid electrolyte and the pH was adjusted to 6.5 with 1 mol / L sodium hydroxide solution to obtain a rainwater-simulated electrolyte.
[0066] (2) Preparation of corrosion three-electrode sensor based on polyacrylamide gel electrolyte.
[0067] First, 2g acrylamide, 0.1g ammonium persulfate, and 2.5mg methylenebisacrylamide were weighed and dissolved in 20mL of rainwater-like electrolyte to obtain a uniform mixed solution. Glycerol with a concentration of 40% W / W was added to the mixed solution, and the mixed solution was deoxygenated with nitrogen for 10 minutes, then heated at 60°C for 30 minutes for polymerization, poured into a cylindrical silica gel mold with a diameter of 40mm and a height of 40mm, and cooled to obtain a polyacrylamide gel electrolyte.
[0068] (3) The polyacrylamide obtained in step (2) is poured into a mold 1 in which a counter electrode 2 and silver / silver chloride as a reference electrode 3 are inserted, and then the mold 1 with the gel electrolyte is placed on the working electrode 4 to form a portable corrosion three-electrode sensor. The distance between the reference electrode 3 and the electrode 4 is 4 mm, and the distance between the counter electrode 2 and the electrode 4 is 5 mm.
[0069] The corrosion three-electrode sensor was electrochemically tested to verify the system and its stability. Figure 7 Three consecutive EIS measurements of the same sample are shown. The results show good stability of the overall measurement.
[0070] Comparative Example 1 Agar gel electrolyte
[0071] (1) Prepare rainwater-like electrolyte
[0072] First, 14.43 mg of calcium sulfate dihydrate (CaSO4·2H2O), 15.04 mg of ammonium sulfate [(NH4)2SO4], 19.15 mg of ammonium chloride [(NH4)Cl], and 15.13 mg of sodium nitrate (NaNO3) were dissolved in 1000 mL of distilled water. The mixed solution was used as a liquid electrolyte and the pH was adjusted to 6.5 with 1 mol / L sodium hydroxide solution to obtain a liquid electrolyte.
[0073] (2) Preparation of a three-electrode corrosion sensor based on agar gel electrolyte
[0074] Agar powder was added to 40 mL of electrolyte at a concentration of 2% W / W, and the solution was stirred at room temperature for 30 min. Then the solution was placed in an oil bath at 110°C for 30 min. After cooling at room temperature for a period of time, the electrolyte was poured into a mold 1 equipped with a carbon rod as a counter electrode 2 and silver / silver chloride as a reference electrode 3, and then cooled to solidify to obtain a corrosion three-electrode sensor. The structure of the corrosion three-electrode sensor is the same as that of Example 1, except that the electrolyte is different.
[0075] Using the above process, the agar contents were 3% W / W, 4% W / W, 5% W / W, 6% W / W, 8% W / W, and 10% W / W, respectively, to obtain 6 groups of corrosion three-electrode sensors based on agar gel electrolyte.
[0076] The electrochemical performance tests were carried out on the 7 groups of agar gel electrolyte corrosion sensors implemented in this case, such as Figure 8 shown. Figure 8 The electrochemical impedance spectra and TAFEL comparison diagrams of 7 groups of corrosion three-electrode sensors based on agar gel electrolyte prepared in Comparative Example 1, wherein A is the electrochemical impedance spectra of the corrosion sensors with gel electrolytes of different agar contents, and B is the corresponding TAFEL diagram. Figure 8 As shown in the figure, all agar concentration curve characteristics are similar, indicating that adding agar content does not significantly change the electrode reaction, thus supporting the use of this gel electrolyte for electrochemical testing. It can be found from the EIS and TAFEL test graphs that when the agar content is 4% W / W, the gel electrolyte has the least effect on the corrosion of the working electrode. It can be seen that the agar gel corrosion sensor prepared at this concentration has the best performance.
[0077] When the corrosion sensor with agar content of 4% W / W was tested for aging, the results showed that after 24 hours, the test results of electrochemical impedance spectroscopy were inconsistent, such as Fig. 9 This suggests that the properties of the agar gel electrolyte may change over time, affecting the stability and accuracy of the sensor.
[0078] Example 7 Practical application of polyacrylamide gel corrosion sensor
[0079] The polyacrylamide gel corrosion sensor prepared in Example 6 and the agar gel corrosion sensor prepared in Comparative Example 1 were used to detect the corrosion of different metal blocks within 24 hours. The details are as follows:
[0080] 316L stainless steel plates, 201 stainless steel plates, and Q235 steel plates with a length of 5 cm, a width of 5 cm, and a thickness of 0.2 cm were used as working electrodes, and ultrasonically treated in acetone, ethanol, and deionized water for 30 minutes each to clean them. The cleaned working electrodes were polished in turn with 280#, 800#, and 1200# sandpapers, and then dried for standby use. The treated 316L stainless steel, 201 stainless steel, and Q235 steel were placed in a constant temperature and humidity test chamber, and corroded for 1h, 4h, 8h, and 24h at a temperature of 15°C and a humidity of 100. The polyacrylamide gel corrosion sensor prepared in Example 6 and the agar gel corrosion sensor prepared in Comparative Example 1 were placed on the above-mentioned steel plate samples, respectively, and then connected to the electrochemical workstation to start the test. Electrochemical impedance spectroscopy tests were performed on the corrosion of 316L stainless steel plates, 201 stainless steel plates, and Q235 steel plates within 1-24h, and the results are as follows Fig.10 shown.
[0081] Fig.10The electrochemical impedance spectra of the portable three-electrode corrosion sensor based on polyacrylamide gel electrolyte and the three-electrode corrosion sensor based on agar gel electrolyte in Example 7 for corrosion of different metal blocks within 24 hours; wherein A is the electrochemical impedance spectrum of the polyacrylamide gel corrosion sensor for 316L stainless steel, B is the electrochemical impedance spectrum of the polyacrylamide gel corrosion sensor for 201 stainless steel, C is the electrochemical impedance spectrum of the polyacrylamide gel corrosion sensor for Q235 steel, D is the impedance test diagram of the agar gel corrosion sensor for 316L stainless steel, E is the impedance test diagram of the agar gel corrosion sensor for 201 stainless steel, F is the impedance test diagram of the agar gel corrosion sensor for Q235 steel, G is the electrochemical impedance spectrum of the corrosion comparison of the polyacrylamide gel corrosion sensor for 316L stainless steel, 201 stainless steel, and Q235 steel at 24 hours, and H is the electrochemical impedance spectrum of the corrosion comparison of the agar gel corrosion sensor for 316L stainless steel, 201 stainless steel, and Q235 steel at 24 hours. From ( Fig.10 It can be found that the A, B, and C show obvious impedance changes. The polyacrylamide gel sensor can clearly reflect the corrosion of different materials at different time points. This shows that the polyacrylamide gel sensor is highly sensitive to metal corrosion and can effectively capture the electrochemical changes in the corrosion process. Test results of agar gel corrosion sensor ( Fig.10 D, E, and F) show weaker electrochemical responses, and it is difficult to distinguish the corrosion differences at different time points. Therefore, when evaluating metal corrosion in a short period of time, the results of polyacrylamide gel are clearer.
[0082] pass Fig.10 The analysis of G and H showed that at the same time, both polyacrylamide gel and agar gel showed that Q235 had a smaller impedance, while 316L had a larger impedance, indicating that 316L had better corrosion resistance. This further verifies the superiority of polyacrylamide gel sensors in metal corrosion assessment.
[0083] The hanging plate method is often used to judge the corrosion condition of samples. Specific operation: ultrasonically treat 316L stainless steel, 201 stainless steel, and Q235 steel in acetone, ethanol, and deionized water for 30 minutes each until they are clean. Use 280#, 800#, and 1200# sandpaper to polish the cleaned working electrodes in turn and then dry them for use. Put the treated 316L stainless steel, 201 stainless steel, and Q235 steel into a constant temperature and humidity test chamber and corrode them at a temperature of 15°C and a humidity of 100. The corrosion condition of the sample within 24 hours is judged by the quality difference. The results are as follows: Fig.11 shown.
[0084] Fig.11The corrosion rate diagram of different metal blocks in Example 7 using the hanging plate method within 24 hours, where A is the sample diagram before corrosion, from left to right are 316L stainless steel, 201 stainless steel, Q235 steel, B is the sample diagram after 24 hours of corrosion, from left to right are 316L stainless steel, 201 stainless steel, Q235 steel, C is the mass weight loss diagram of 316L stainless steel, D is the mass weight loss diagram of 201 stainless steel, and E is the mass weight loss diagram of Q235 steel. Fig.11 In the comparison of A and B, the changes in the samples observed with the naked eye cannot accurately determine the corrosion situation, especially when there are no obvious signs of corrosion on the surface. Fig.11 C, D and E), the corrosion degree of each material can be evaluated more objectively. Fig.10 It can be seen that Q235 steel has the largest mass loss and a higher corrosion rate, while 316L stainless steel exhibits better corrosion resistance.
[0085] Although the coupon method is an effective corrosion assessment method, it is complicated to operate and requires a long wait time, and may not be suitable for occasions that require rapid assessment. Compared with the coupon method, the polyacrylamide gel electrolyte sensor of the present invention provides a more efficient detection method. By directly performing electrochemical tests, we can quickly obtain electrochemical impedance spectroscopy data and then compare the corrosion resistance of different metals. The experimental results show that the results of the gel sensor are consistent with the coupon method, indicating its accuracy and reliability.
[0086] In summary, the gel corrosion sensor is simpler and faster to operate, can effectively reduce the experimental waiting time, and is suitable for occasions where metal corrosion performance needs to be quickly evaluated. Therefore, the gel electrolyte sensor is a corrosion detection method worthy of promotion.
Claims
1. A polyacrylamide gel electrolyte, characterized in that: The polyacrylamide gel electrolyte comprises acrylamide monomer, initiator, crosslinking agent and glycerol as raw materials, and the acrylamide monomer is dissolved in water phase, the initiator and crosslinking agent are added, and the acrylamide is initiated by the initiator to undergo free radical polymerization under anaerobic conditions.
2. The polyacrylamide gel electrolyte according to claim 1, characterized in that: The initiator is ammonium persulfate or potassium persulfate, the crosslinker is methylenebisacrylamide, the concentration of acrylamide monomer in the water phase is 10-50%, the amount of the initiator is 4-6% of the monomer mass, and the amount of the crosslinker is 0.01-0.5% of the monomer mass.
3. The polyacrylamide gel electrolyte according to claim 1, characterized in that: The aqueous phase is a sodium sulfate solution or a rain-like water solution. The concentration of the sodium sulfate solution is 0.002-1 mol / L, and the concentration of the total solute in the rain-like water solution is 0.0005-0.05 mol / L.
4. The method for preparing the polyacrylamide gel electrolyte according to any one of claims 1 to 3, characterized in that: The following steps are involved: Dissolve acrylamide in water phase, add initiator, crosslinker, glycerol and sodium sulfate solution, stir evenly, bubble inert gas for 10-20 minutes, place at 60-100° C. for 30-60 minutes, and cool to room temperature to obtain polyacrylamide gel electrolyte.
5. Use of the polyacrylamide gel electrolyte according to any one of claims 1 to 3 in the preparation of a portable corrosion three-electrode sensor.
6. A portable three-electrode corrosion sensor based on the polyacrylamide gel electrolyte according to any one of claims 1 to 3, comprising an outer layer mold (1), characterized in that: The outer layer mold (1) contains the polyacrylamide gel electrolyte (5) according to any one of claims 1 to 4, a counter electrode (2) and a reference electrode (3) are inserted into the polyacrylamide gel electrolyte (5) according to any one of claims 1 to 4, and a working electrode (4) is provided at the bottom of the polyacrylamide gel electrolyte (5) according to any one of claims 1 to 4.
7. The portable three-electrode corrosion sensor according to claim 6, characterized in that: The outer layer mold (1) is made of epoxy resin and hardener, the reference electrode (3) is a silver / silver chloride electrode, a silver wire electrode or a silver-plated silver wire electrode, the electrode (2) is a carbon rod or a carbon plate, and the working electrode (4) is a stainless steel sheet.
8. The portable three-electrode corrosion sensor according to claim 6, characterized in that: The reference electrode (3) is arranged in parallel with the counter electrode (2), and the bottom end of the reference electrode (3) is 2 to 6 mm away from the upper surface of the working electrode (4).
9. The portable three-electrode corrosion sensor according to claim 6, characterized in that: The outer layer mold (1) is made by mixing epoxy resin and hardener and pouring it into a silicone mold and letting it stand for 24 to 48 hours. The working electrode (4) needs to be pretreated. The pretreatment steps include: ultrasonically treating the working electrode (4) in acetone, ethanol, and deionized water for 20 to 40 minutes each to clean it, and polishing the cleaned working electrode (4) with 280#, 800#, and 1200# sandpaper in turn. The polished working electrode (4) is dried at 40 to 60°C for 1 to 2 hours.
10. Use of the polyacrylamide gel electrolyte according to any one of claims 1 to 3 or the portable corrosion three-electrode sensor according to any one of claims 6 to 9 in atmospheric corrosion monitoring.
Citation Information
Patent Citations
Rapid corrosion measuring pen and testing method thereof
CN113686771A
Gel electrolyte capable of being used for lithium ion battery, preparation method of gel electrolyte and lithium ion battery
CN116387643A
Atmospheric corrosion thin liquid film experimental device and experimental method for electrified metal conductor
CN117686416A